Corporate Social Responsibility Reporting and Financial Market Performance - Teppo, Anna-Leena (My University, 2007)
The roles and responsibilities of business in society have been going through significant changes during past decades. In addition to the traditional bottom line; creating value to shareholders, the companies are asked to be accountable for a changing set of corporate social responsibility (CSR) issues and thus contributing to local as well as global sustainable development. Companies have responded to this growing demand for CSR by publishing more information related to their social and environmental responsibility. This study examined whether there exists a relationship between such social and environmental disclosure and the financial market performance of a company. Thus the study addressed a question whether investors care about the CSR reporting of companies so that their appreciation of a larger amount of reporting could be seen through improved share price performance. The final sample consisted of 80 Finnish and Swedish companies listed in the Nordic Exchange. By using the method of content analysis the CSR data component was obtained form companies’ annual reports and separately published CSR reports from years 2001-2007. Share returns were calculated from share price data obtained from Datastream database. The results from the series of statistical testing with Pearson correlation coefficients, Chi- Square test of association and analysis of co-covariance indicated that the answer to the research question is no. None of the findings proved to be statistically significant and thus there still seems to be a contradiction between the investors’ increasing demand for CSR disclosure and the appreciation of this disclosure since there still exist no evidence of proven links between the price sensitivity of the social and environmental data.
Keywords: corporate social responsibility reporting; corporate sustainability; financial market performance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|